2017
DOI: 10.4103/1117-6806.205751
|View full text |Cite
|
Sign up to set email alerts
|

Civilian penetrating gunshot injury to the neurocranium in Enugu

Abstract: Introduction:Civilian penetrating gunshot injuries to the neurocranium are no longer uncommon in Nigeria. Such injuries are however poorly reported. They are associated with poor outcome and, at close range, are frequently fatal, especially when inflicted by high-velocity weapons. Prompt transfer to neurosurgical service and urgent intervention may improve outcome in those that are not mortally wounded.Materials and Methods:Fifty-two patients with civilian penetrating gunshot wounds seen over a 10-year period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…Interestingly, our numbers, with regard to gunshot injuries in pediatric patients, are similar to a report from South Africa [14]. Like other previous studies [6,9,13,[15][16][17], our data revealed that males were disproportionately affected, and this could be explained by their outdoor presence most of the time because of societal gender roles.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, our numbers, with regard to gunshot injuries in pediatric patients, are similar to a report from South Africa [14]. Like other previous studies [6,9,13,[15][16][17], our data revealed that males were disproportionately affected, and this could be explained by their outdoor presence most of the time because of societal gender roles.…”
Section: Discussionsupporting
confidence: 89%
“…This was made up of 37 males and 4 females giving a male: female ratio of 9.25: 1. The finding of a large male preponderance in this study has been the general trend in the literature over the years [ 2 , 6 , 13 , 15 , 16 , 18 , 22 , 24 , 27 - 29 ]. The reasons for this trend have been attributed by many authors to the fact that males are usually the bread winners, take more risks, are more outgoing and thus more involved in the activities that predispose to GSI including wars, armed robbery, communal clashes, political thuggery etc.…”
Section: Discussionsupporting
confidence: 80%